Impact of rooftop garden and shading effect towards human thermal comfort - Shathiran, Muhammad Irfan; Osman, Muhammad Syahir; Ab Sani, Jasasikin (2015)
Human thermal comfort is an indicator for satisfaction of human towards the thermal factor in the environment. This topic may be a subjective matter due to the different characteristics of human to reach a certain level for obtaining the same satisfaction of thermal comfort. Factors that are looked into through this study are surface temperature, and solar radiation. Data collected through these factors, are then further supported by photographical observations, which are done simultaneously with questionnaires to relate and display the environment condition with the human thermal comfort. Questionnaires are distributed in order to gauge the statistics of several groups of people to compare between their characteristics and their level of thermal comfort. Site chosen for rooftop garden was the ‘Secret Garden’ 1 Utama and to contrast it is the plain rooftop of Lot10 and the rooftop parking of Sungei Wang Plaza, Kuala Lumpur. As for urban square, the research was conducted at Standard Charted KL Park. Our results came up with a conclusion that areas that are covered with dense green canopies like rooftop gardens and large vegetation are crucial to provide high level of thermal comfort towards human beings.